Prevention Of Mental Health Problems Among School-Age Children Through Establishment Of Mental Health Alert School - Ridhoyanti Hidayah (Journal of Innovation and Applied Technology, 2021)
Many things cause mental health problems when children are at school. It is not known by both parents and the school. Therefore, it harms student behavior and academic achievement. These impacts can be addressed through education and training for teachers, staff, parents, and students on promotive and preventive measures for mental health problems. This effort is carried out through collaboration among schools, parents, students, and health workers continuously. The results of the activity showed that most parents, teachers, staff, and students did not know about mental health problems, as well as prevention and early handling efforts that could be carried out. Some teachers still have the old paradigm of mental health problems, so the prevention and treatment in overcoming deviant student behavior are still focused on short-term outcomes.